A Comparison of Two Supplementary Doses of Vitamin A on Performance, Intestine and Immune Organ Development, as well as Gene Expression of Inflammatory Factors in Young Hy-Line Brown Laying Pullets - Qinliang Chen; Xiaoqing Han; Huiling Zhu; Yulan Liu; Xiao Xu (Animals, 2022)
The objective of this study was to compare two supplementary doses (6000 vs. 12,000 IU/kg) of vitamin A (VA) on the performance, development of intestine and immune organs, as well as gene expression of inflammatory factors in young Hy-Line Brown laying pullets. A total of 288 one-day-old Hy-Line Brown laying pullets (weighing 42.15 ± 0.23 g) were allotted into two treatments with 12 replicate cages and 12 birds per cage. During the 35-day period, the pullets were fed a basal diet supplemented with different doses of VA (6000 IU/kg VA in control group; 12,000 IU/kg VA in treatment group), respectively. The results showed that supplementary high doses of VA reduced the feed-to-gain ratio from day 21 to 35 (p < 0.05). Moreover, the pullets fed high doses of VA diets had increased length and relative weight of duodenum, jejunum, and ileum (p < 0.05). From observations on morphology, high doses of VA diets increased the villus height and the ratio of villus height to crypt depth in the jejunum and ileum (p < 0.05). High doses of VA diets also increased the relative weight of immune organs (p < 0.05). Furthermore, the gene expressions of inflammatory factors were decreased in the thymus of the pullets fed high doses of VA diets (p < 0.05). In summary, supplementary 12,000 IU/kg doses of VA improved performance and intestine and immune organ development, and alleviated gene expressions of inflammatory factors in young Hy-Line Brown laying pullets.